Cu(In, Ga)Se2 thin films annealed with SnSe2 for solar cell absorber fabricated by magnetron sputtering. (October 2017) - Yan, Yong; Guo, Tao; Song, Xiaohui; Yu, Zhou; Jiang, Yurong; Xia, Congxin
Graphical abstract: Highlights: SnSe2 powders were used to post anneal CIGS thin films deposited by magnetron sputtering. High quality CIGS absorber annealed with SnSe2 led to the device efficiency of 6.21%. The thermal stability of SnSe2 was investigated by TGA and DSC analysis. Gaseous Se2 clusters released from SnSe2 surface and then incorporated with CIGS precursor. Abstract: SnSe2 powders were used to post anneal Cu(In, Ga)Se2 (CIGS) thin films deposited by magnetron sputtering from a quaternary target. First, the thermal stability of SnSe2 was investigated by thermogravimetric analysis (TGA) and differential scanning calorimetric (DSC) analysis, respectively. High temperature, ranging from 413 °C to 625 °C, leads to the decomposition of SnSe2, resulting in the evaporation of Se2 clusters. Then, CIGS precursors and SnSe2 powders were placed in the middle and upstream side of the quartz tube, respectively. A dense and smooth CIGS film with large grain size (∼500 nm) were successfully produced after annealing with SnSe2 . Improvement of the Se2 concentration in the annealing atmosphere is expected to improve the crystalline quality and photovoltaic performance. It is evidenced that the use of SnSe2 as Se-source is feasible and effective for the annealing of solar cell absorber layers.